科隆蛋扣件钢轨波磨演化对车轨系统的影响 - 雷震宇; 徐瑶; 王志强; 赵阳; 李莉 (Jixie qiangdu)
By using the multi-body dynamics software UM,a vehicle-track coupling dynamic model based on the flexible track was established.The superposition model based on the friction work theory was used to study the characteristics frequency of the rail corrugation evolution of Cologne-egg fasteners and its effects on the vertical vibration of the vehicle-track system.The results show that the characteristic frequency of corrugation remains the same at different speeds,which reflects the fixed frequency characteristics of rail corrugation.During the evolution trend of rail corrugation,with the increase of speed,in the middle and high frequency bands,the difference of the vertical vibration of the car body gradually becomes smaller,while the bogie is the opposite.Speed has little effect on the vibration change of the track structure.The maximum vertical magnitude of the rail appears at 160 Hz,while the maximum of the track slab appears at the low frequency band of 16 Hz ～ 31.5 Hz.